Synchronous pleomorphic adenoma in parotid gland and parapharyngeal space: a case report and literature review - Zahid, Hira; Khan, Imran Mohib (Journal of the Pakistan Medical Association, 2023)
Synchronous pleomorphic adenoma in the parotid gland and parapharyngeal space are rare. We report a case of simultaneous pleomorphic adenoma in parotid gland and parapharyngeal space in a 65-year-old male presenting to the ENT outpatient department at Northwest General Hospital, Peshawar. The patient presented with a left parotid lump, intra oral examination of which revealed the left palatine tonsil to have been pushed medially. CT of the neck showed a completely separate lump in the left parapharyngeal space, and FNAC of the parotid lump was suggestive of mucoepidermoid carcinoma. The superficial parotid lump was excised first, and the parapharyngeal growth was accessed intraorally and excised. Histopathology revealed both the growths to be pleomorphic adenomas. It is important to raise awareness of synchronous salivary gland tumours, which are a rare occurrence, to highlight its optimal investigation to ensure complete surgical excision, and appropriate management.